Penentuan Laju Infiltrasi Tanah pada Beberapa Kondisi Vegetasi di Kebun Raya ITERA - Faradila Mei Jayani; Silvi Novianti (Jember University Press, 2023)
Measuring the rate of infiltration in an area is important as one of the basic actions for land management. The existence of infiltration allows the soil to temporarily store water so that it is available for absorption by plants and soil organisms. The ITERA Botanical Gardens, which aims to conserve Sumatran plants ex-situ, needs to be supported by successful revegetation. The infiltration rate is an indicator of the physical condition of the soil during the revegetation process. The purpose of this study was to calculate the soil infiltration rate in the ITERA Botanical Gardens under different vegetation conditions, namely under sengon (Falcataria moluccana) and grass stands. This research is an experimental study that measures the rate of soil infiltration using a double ring infiltrometer with a diameter of 15 cm and 30 cm. The infiltration rate was then calculated based on data on changes in water level over time intervals (âˆ†h) and changes in measurement time intervals (âˆ†t) obtained from field measurements. Infiltration in the area of ITERA Botanical Gardens is influenced by the condition of the vegetation above the ground. Lowering of the water level in the ring on grassy land reaches a constant faster than under sengon stands. The infiltration rate under Albizia stands is faster than on land with grassy vegetation. This requires the act of planting vegetation that has deep roots, on land that is still planted with grass.